L’Ecole Sucrière Belge de Glons - Deelstra, Hendrik; Peters, Michel (Studium, 2008)
The Belgian sugar school of Glons This article deals with the start in 1889 and the evolution till 1914 of the first Sugar technical school in Belgium located in Glons-Liège. In the literature on the history of sciences in Belgium this school has been unjustly neglected or forgotten. This is probably due to the total destruction of the archives in 1917 by the German occupiers. The history of the creation of a School for sugar chemists and technicians goes back to the early 1880’s, when the need was realised for the creation of such a High Technical School, to support and improve the most important agro-industrial industry in Belgium: the beet-sugar production. However there was at that time no consensus how to create and organize such an Institute. In 1889, E. Nihoul started in Glons a private sugar technical school for the direct training of specialists for all functions in the sugar industry, especially that of sugar chemists. This article describes the history of this school from 1889 till 1914. The school rapidly gained a great reputation and became extremely attractive for students outside Belgium. During the period 1900 till 1914 the school produced 251 qualified specialists of which 80% were foreigners. The school moved to Liège in 1917 and after 1932 involved in fusions with different Technical High Schools to form the now well-known ‘Hautes Ecoles Rennequin Sualem’ in Liège.